Optimizing the Success of Hospital Management Information Systems in the Digitalization Era - Amalia, Rizkiyatul; Lestari, Sri (Procedia of Engineering and Life Science, 2024)
Digitalization has changed aspects, one of which is in the Healthcare sector. Digitalization will help organizations overcome the problem of limited resources. Hospital management information systems (HMIS) are becoming increasingly important in operational, clinical, and administrative management. Although many hospitals have adopted HMIS, not all systems have successfully achieved their goals. Some common problems include data integration difficulties, user resistance, and lack of management support. Accurate and complete data is key to the success of HMIS. However, hospitals still face challenges in managing data quality. HMIS can provide valuable data to support strategic and operational decision-making. However, existing data has not been optimally utilized. The study aims to analyze how system quality affects HMIS Implementation. This study used an analytic observational method conducted at Dr. Gondo Suwarno Hospital. The sample consisted of 65 HMIS users. Data analysis in this study used SEM (Structural Equation Modeling) analysis techniques. The application used is Smart Partial Least Square (SmartPLS). The results showed that the quality of the system on the implementation of HMIS through System Use and Organizational Structure provides a negative value. The path coefficient values obtained are -0.005 and -0.048 and the P-value is 0.722 and 0.256. The implication of this result is that system quality should be able to increase system usage, in the context of this study, the quality of the existing system is not enough to encourage users to be more active in using HMIS. This may be due to other factors such as lack of adequate training or technical support for users. system quality did not contribute significantly to the organizational structure that supports the implementation of HMIS. Although the existing system has certain qualities, the existing organizational structure may not be supportive enough to facilitate effective implementation.